1999
DOI: 10.1002/lt.500050105
|View full text |Cite
|
Sign up to set email alerts
|

Candida infection in pediatric liver transplant recipients

Abstract: A retrospective review of 100 liver transplantations in 98 children was performed to determine the incidence of infection caused by Candida organism in these patients and to identify risk factors that may predispose to serious fungal infection. Thirty-one infections caused by Candida organisms developed during the initial 28 days posttransplantation: 19 were definite invasive infections (one deep site or one positive blood culture), 2 were probable invasive infections (three superficial sites), and 10 were uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
45
3
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 16 publications
8
45
3
4
Order By: Relevance
“…Other risk factors for bacterial infections included surgical issues and technical complexity of surgery, which is in accordance with previous reports. 8,22,24,25,34 We and others found that preoperative ascites was an independent risk factor for fungal infection. 35 This can be attributed to patients with preoperative ascites who are usually malnourished and more susceptible to fungal infection, as noted by A total of 3 cases had no definite organism and were diagnosed by chest x-ray and CT. 8 ; moreover, we also found that prolonged insertion of an intravascular catheter was an independent risk factor for fungal infection.…”
Section: Discussionmentioning
confidence: 82%
“…Other risk factors for bacterial infections included surgical issues and technical complexity of surgery, which is in accordance with previous reports. 8,22,24,25,34 We and others found that preoperative ascites was an independent risk factor for fungal infection. 35 This can be attributed to patients with preoperative ascites who are usually malnourished and more susceptible to fungal infection, as noted by A total of 3 cases had no definite organism and were diagnosed by chest x-ray and CT. 8 ; moreover, we also found that prolonged insertion of an intravascular catheter was an independent risk factor for fungal infection.…”
Section: Discussionmentioning
confidence: 82%
“…Many reports have been published about risk factors for invasive fungal infection in recipients of deceased donor liver grafts (Gladdy et al 1999;Fortun et al 2002); on the other hand, there have been no reports about the risk factors for living donor liver transplantation (LDLT). Most LDLTs are elective surgery, thus it is possible to treat pre-existing infections and prepare the patient by administering prophylactic agents.…”
mentioning
confidence: 99%
“…Likewise, the development of bile leaks and bowel perforations are associated with polymicrobial intraabdominal infections in the first month after LTx. 25 Finally, re-exploration of the abdomen is associated with increased rates of fungal infection. 13 Intermediate Period Days)…”
Section: Early Infections (0-30 Days)mentioning
confidence: 99%
“…The recovery of Candida from a JacksonPratt drain in the early postoperative period may occur prior to the onset of clinical symptoms of intra-abdominal infection. 25 Such a recovery should prompt initiation of antimicrobial therapy and an aggressive evaluation of the presence of the source of the infection. Early initiation of treatment is particularly important, given an attributable mortality rate of up to 33% for Candida infections in pediatric liver transplant recipients.…”
Section: Bacterial and Fungal Infectionsmentioning
confidence: 99%
See 1 more Smart Citation